Better wear red? The influence of the color of sportswear on the outcome of Olympic sport competitions - Hilgarth, M. N. (2020)
The existence of biological and psychological effects of colors has been well documented in animals and humans. Based on these findings, various researchers postulated that the color of the sportswear does affect the outcome of sporting competitions. If this is true, this would have enormous consequences for tournaments. The aim of this thesis was to expand previous research to test this claim. In order to do so, data for three different sports (boxing, taekwondo and wrestling) was gathered for the five Olympic tournaments between 2000 and 2016. This thesis does not find any evidence supporting the claim that red sportswear is a competitive advantage in competitions. The results are consistent over different sports, sexes and geographical distinctions. While this conclusion is reassuring for the design of existing tournaments, it also highlights the the need for replications in the scientific process.